Heterogeneity of characteristics, structure, and dynamics of male and hijra sex workers in selected cities of Pakistan. (20th April 2013) - Thompson, Laura H; Salim, Momina; Baloch, Chaker Riaz; Musa, Nighat; Reza, Tahira; Dar, Nosheen; Arian, Shahzad; Blanchard, James F; Emmanuel, Faran
Abstract : Background: We sought to describe the characteristics and operational dynamics of male sex workers (MSW) and hijra sex workers (HSWs) in 11 cities across Pakistan in 2011. Methods: We report descriptive statistics of self-reported sexual behaviour data from cross-sectional mapping and biological and behavioural surveys conducted among 1431 MSWs and 1415 HSWs in four cities across Pakistan in 2011. Results: While Karachi had the largest numbers of MSWs and HSWs, Quetta had the largest relative population sizes, with 3.6 MSWs per 1000 male adults and 3.3 HSWs per 1000 male adults. There was considerable variability in the proportion of HSWs who operate through deras, ranging from 2.2% in Peshawar to 62.7% in Karachi. The number of HSWs per guru varies by city, from 1.5 in Quetta to 16.5 HSWs per guru in Karachi. Among HSWs, the use of mobile phones for solicitation ranged from 37.6% in Quetta to 83% in Peshawar and among MSWs the use of mobile phones ranged from 27% in Karachi to 52% in Quetta. In Quetta, a large proportion of HSWs (41%) find clients through gurus . Client volume tended to be higher among HSWs and among both MSWs and HSWs in Quetta and Peshawar. Condom use with clients was most consistent in Quetta, with 31% of MSWs and 41% of HSWs reporting always using condoms with clients. Peshawar had the greatest proportion reporting never using condoms. Conclusions: There is considerable geographic heterogeneity in the characteristics and operational dynamics of MSWs and HSWs across Pakistan.